(untitled) (Journal of Engineering, 2016)
This study involves the design of 24 mixtures of fiber reinforced magnetic reactive powder concrete containing nano silica. Tap water was used for 12 of these mixtures, while magnetic water was used for the others. The nano silica (NS) with ratios (1, 1.5, 2, 2.5 and 3) % by weight of cement, were used for all the mixtures. The results have shown that the mixture containing 2.5% NS gives the highest compressive strength at age 7 days. Many different other tests were carried out, the results have shown that the carbon fiber reinforced magnetic reactive powder concrete containing 2.5% NS (CFRMRPCCNS) had higher compressive strength, modulus of rupture, splitting tension, stress in compression and strain in compression than the corresponding values for the carbon fiber reinforced nonmagnetic reactive powder concrete containing the same ratio of NS (CFRNRPCCNS). The percentage increase in these values for CFRMRPCCNS were (22.37, 17.96, 19.44, 6.44 and 25.8) % at 28 days respectively, as compared with the corresponding CFRNRPCCNS mixtures.